Pathology of Cyber Threats (Instagram) Among Adolescents - Talebdoost, Maryam; Amirpour, Mahnaz; Imanian Ardabili, Masoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The objective of the present study was to investigate the pathology of cyber threats (Instagram) among adolescents. Methods and Materials: The research method was qualitative with thematic analysis and applied in nature. The participant community included 13 experts in the field of cyberspace who were selected through purposive sampling. The research tool was semi-structured interviews. The validity of the data was examined through face validity and by other experts, and the reliability was assessed using the recoding method, resulting in a reliability score of 0.83. Data analysis was conducted manually using the coding method. Findings: The findings identified 29 threats, including time-wasting, weakening beliefs, individual isolation, personality weakness, reduced individual abilities, decreased family relationships and interactions, cultural challenges and conflicts, incompatibility with family, abnormal behaviors within the family environment, emotional detachment from family, reduced real social relationships, changes in beliefs and cultural patterns, breaking societal norms - responsibility evasion and creation of social problems, academic decline, reduced study time, academic theft, promotion of sexual corruption - sexual crisis, early maturity, sexual deviation, and dissemination of harmful sexual information as the harms of cyberspace (Instagram). These were categorized into core codes (individual, familial, educational, social, and sexual harms). Conclusion: It can be concluded that cyberspace, despite its numerous and impactful opportunities in life, also has various harms that can be mitigated through planning and education on the correct use of cyberspace, particularly Instagram.